Geographic distribution of CDA-II: did a founder effect operate in Southern Italy? - A Iolascon; V Servedio; R Carbone; A Totaro; M Carella; S Perrotta; SN Wickramasinghe; J Delaunay; H Heimpel; P Gasparini (Haematologica, 2000)
BACKGROUND AND OBJECTIVE: Congenital dyserythropoietic anemia type II (CDA-II) is an autosomal recessive condition, whose manifestations range from mild to moderate. Its exact prevalence is unknown. Based on a recently established International Registry of CDA-II (64 unrelated kindreds), a high frequency of CDA II families living in South Italy became evident. DESIGN AND METHODS: The aim of this study was to define the haplotypes of the CDA II kindreds living in Southern Italy based on markers D20S884, D20S863, RPN, D20S841 and D20S908. These markers map to 20q11.2, within the interval of the CDAN2 gene that is responsible for CDA II. Next, we looked at these markers in kindreds from other regions of Italy and from other countries, with special attention to families having ancestors in Southern Italy. RESULTS: Evaluation of the geographic distribution of the ancestry of Italian CDA-II patients clearly demonstrated the unusually high incidence of this condition in Southern Italy. Our statistical calculations and linkage disequilibrium data also clearly demonstrate a strong association of the markers of chromosome 20 with the disease locus in our sample. Almost all the regions defined by the markers here used is in disequilibrium with the disease. Combining the data from the Italian sample together with those obtained from the non-Italian ones, we can restrict the area of highest disequilibrium to that defined by markers D20S863-D20S908. INTERPRETATION AND CONCLUSIONS: Despite the presence of this linkage disequilibrium the search for a common haplotype failed. This could suggest that the mutation was very old or that it occurred more than once on different genetic backgrounds.